2005
DOI: 10.1103/physrevb.72.073404
|View full text |Cite
|
Sign up to set email alerts
|

Band-gap formation in(n,0)single-walled carbon nanotubes(n=9,12,15,18

Abstract: We study the electronic structure of the carbon nanotube theoretically by the first-principles techniques using the local-density approximation ͑LDA͒ with the many-body correction in the GW approximation. We find that the ͑9,0͒ tube is gapful irrespective of naive expectation from the graphene band structure. All of thehybridization effect, lattice relaxation effect, and many-body effect due to electron interaction enhance the band gap, and the value is as large as 0.17 eV when taking into account all effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
5
26
0
Order By: Relevance
“…Energy bands of a ͑9,0͒ zigzag tube were previously calculated in a local-density approximation with many-body correction in a GW approximation. 59 In the absence of the many-body correction, the band gap after geometry relaxation is 0.12 eV, and the many-body correction enhances it by 40% to 0.17 eV. The present calculation gives much larger enhancement of factor 2 ϳ 2.5 for 0.1 Ͻ ͑e 2 / L͒͑2␥ / L͒ −1 Ͻ 0.2, as shown in Fig.…”
Section: Discussionsupporting
confidence: 47%
“…Energy bands of a ͑9,0͒ zigzag tube were previously calculated in a local-density approximation with many-body correction in a GW approximation. 59 In the absence of the many-body correction, the band gap after geometry relaxation is 0.12 eV, and the many-body correction enhances it by 40% to 0.17 eV. The present calculation gives much larger enhancement of factor 2 ϳ 2.5 for 0.1 Ͻ ͑e 2 / L͒͑2␥ / L͒ −1 Ͻ 0.2, as shown in Fig.…”
Section: Discussionsupporting
confidence: 47%
“…Subsequently GW calculations have been employed as a firstprinciples method for a broad array of real materials, 6-8 the physical systems ranging from bulk semiconductors 13 to nanoclusters [14][15][16] and nanotubes. 17,18 As the field has advanced, the methodology has been extended to include approximate self-consistency in the Green's function [19][20][21][22] and the role of vertex corrections is currently under debate, [23][24][25] both at the expense of further computational burden.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this trend is in contrast to that of semiconducting CNTs. It has already been showed that the band gap of semiconducting CNTs inversely depends on the nanotube diameter [31,32]. It is known that the change of E g influences the nanotube reactivity.…”
Section: Resultsmentioning
confidence: 99%